National Implementation of Acute Stroke Care Centers in the Veterans Health Administration (VHA): Formative Evaluation of the Field Response - Damush, Teresa M. (J Gen Intern Med, 2014)
BACKGROUND: In 2011, the Veterans Health Administration (VHA) released the Acute Ischemic Stroke (AIS) Directive, which mandated reorganization of acute stroke care, including self-designation of stroke centers as Primary (P), Limited Hours (LH), or Supporting (S). OBJECTIVES: In partnership with the VHA Offices of Emergency Medicine and Specialty Care Services, the VA Stroke QUERI conducted a formative evaluation in a national sample of three levels of stroke centers in order to understand barriers and facilitators. DESIGN AND APPROACH: The evaluation consisted of a mixed-methods assessment that included a qualitative assessment of data from semi-structured interviews with key informants and a quantitative assessment of stroke quality-of-care data reporting practices by facility characteristics. PARTICIPANTS: The final sample included 38 facilities (84 % participation rate): nine P, 24 LH, and five S facilities. In total, we interviewed 107 clinicians and 16 regional Veterans Integrated Service Network (VISN) leaders. RESULTS: Across all three levels of stroke centers, stroke teams identified the specific need for systematic nurse training to triage and initiate stroke protocols. The most frequently reported barriers centered around quality-of-care data collection. A low number of eligible veterans arriving at the VAMC in a timely manner was another major impediment. The LH and S facilities reported some unique barriers: access to radiology and neurology services; EMS diverting stroke patients to nearby stroke centers, maintaining staff competency, and a lack of stroke clinical champions. Solutions that were applied included developing stroke order sets and templates to provide systematic decision support, implementing a stroke code in the facility for a coordinated response to stroke, and staff resource allocation and training. Data reporting by facility evaluation demonstrated that categorizing site volume did indicate a lower likelihood of reporting among VAMCs with 25–49 acute stroke admissions per year. CONCLUSIONS: The AIS Directive brought focused attention to reorganizing stroke care across a wide range of facility types. Larger VA facilities tended to follow established practices for organizing stroke care, but the unique addition of the LH designation presented some challenges. S facilities tended to report a lack of a coordinated stroke team and champion to drive process changes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11606-014-3036-1) contains supplementary material, which is available to authorized users.